Self Efficacy on Mathematics Learning Outcomes of Elementary School Students The Impact of Online Learning - Mahmudah, Wahyu Nitasari; Hermanto (Jurnal Pendidikan Indonesia, 2024)
Since the COVID-19 pandemic spread in Indonesia, all educational units have implemented distance learning programs. Students are required to understand the material and submit assignments online. This results in the need for us to know students' difficulty levels and self-efficacy during online learning. Besides that, online learning makes measuring students' affective abilities difficult. One of the affective abilities that students need to have is self-efficacy. This study aims to analyze the influence of self-efficacy on the mathematics learning outcomes of fifth-grade elementary school students. This type of research is quantitative research. The sample for this research was 60 elementary school students in Ayah District using expo facto research. This research uses a quantitative approach with data collection techniques using a psychological scale. The analysis technique uses simple linear regression, and prerequisite tests have been previously carried out in the form of normality tests, linearity tests, and heteroscedasticity tests. Based on the research results, it can be seen that self-efficacy has a significant influence of 63.7% on mathematics learning outcomes. However, it is known that when face-to-face learning is limited, students have not fully mastered the material and subject matter studied previously.